Faktor-Faktor Yang Mempengaruhi Penggunaan Mobile Banking Pada Layanan BSI Mobile Dengan Menggunakan Model Unified Theory Of Acceptance And Use Of Technology (UTAUT) - Pohan, Rahma Nur Azizah; Rokan, Mustapa Khamal; Syarvina, Wahyu (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This study aims to see how the level of acceptance and use of the BSI mobile service system is measured using the UTAUT (Unified Theory Of Acceptance and Use Of Technology) model and find out what are the factors that influence customers in using BSI mobile services to students of the Faculty of Economics and Business. Islamic Business, State Islamic University of North Sumatra, batch 2018. This study has a sample of 100 students using a quantitative approach obtained from primary data sourced from customer survey results and secondary data. The data analysis techniques used are Descriptive Statistical Analysis, Validity Test, Reliability Test, Normality Test, Kolmogorov-Smirnov Test, Multicollinearity Test, Heteroscedasticity Test, t Test, F test, coefficient of determination test and multiple linear regression test using SPSS 25. So the results of data analysis on the hypothesis testing of performance expectations and social influence do not have a positive effect, then the variables of business expectations and condition of facilities have a positive effect.